Experimental Analysis of Heat Storage and Release of Binary Methanol Aqueous Solution Pulsating Heat Pipe Phase Change Accumulator - Lu, Xiaohui; Luo, Xiaoxue; Cao, Shibo; Zou, Changzhen (Frontiers in Energy Research, 2022)
To improve the problems of energy shortage and low utilization rate, this paper designed a set of pulsating heat pipe (PHP) devices coupled with phase change energy storage material. Further, the binary methanol-water solution is proposed as a novel experimental filling medium to enhance the heat transfer performance of the device. The fluid flow model of the PHP was analyzed via experiment and simulation. Besides, the heat storage and release performances of the PHP at different flow rates, different heating temperatures, different filling mediums, and different filling ratios are investigated. The results show that when the filling medium (binary methanol-water solution) possesses the filling ratio of 0.6 (methanol and water are each 0.3), the heat source inlet flow is 0.60 m3/h, the heat source heating temperature is 120°C, and the PHP is at the best heat storage performance. During the exothermic process, the lower the initial temperature of cooling water, the higher the heat recovery rate. Thus, it can be concluded that the selection of an appropriate filling medium and the optimal parameters to enhance heat transfer can have a broader application prospect in the field of waste heat recovery.